Digital Revolution in Sustainable Business Models and Finance Management - Jabłoński, Adam; Jabłoński, Marek; Zarzecki, Dariusz (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
At present, the digital economy is creating a new approach to sustainable development. In particular, this relates to the transformation of the traditional economy via the influence of digitalization on finance management processes. The digital economy is affecting changes in resource management processes. Dynamic digital transformation processes are currently taking place and exerting influence on the shaping of new business models. Existing business models are changing, particularly in the context of their life cycle. The new economic model is rendered social factors more important in terms of creating value for people and the natural environment. Trust in financial institutions, which is also a factor in sustainable business models, is an important criterion for business research. Economic model based on the irresponsible use of natural resources have been heavily criticized for years, and societies have begun to reject business models that negatively impact the environment. The aim of this Special Issue is to present the results of research on the current trends and challenges related to the digital revolution in financial management for sustainable development, an issue that requires extensive research and analysis.